Preparation method of bimetallic MnFe-N-C monatomic nano-enzyme and application of bimetallic MnFe-N-C monatomic nano-enzyme in SCN-detection and dye degradation

Through the preparation of bimetallic MnFe-N-C single-atom nanoenzyme, it is used for SCN-detection and dye degradation, the problem of long detection time and limited pH range in the dye degradation process in the prior art is solved, and the rapid and high sensitivity is achieved Detection and degradation effects.

CN119114129APending Publication Date: 2024-12-13GUIZHOU MEDICAL UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411245188.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing SCN-detection methods are time-consuming, complex and expensive, and have limited pH range during dye degradation and difficult catalyst recovery, which limits the practical application of Fenton-like systems.

Method used

Using the preparation method of bimetallic MnFe-N-C single-atom nanoenzyme, MnFe-N-C is prepared by preparing bimetallic metal frame material ZIF-MnFe and heating under argon atmosphere to obtain MnFe-N-C. It is used for colorimetric detection of SCN- and dye degradation. Its highly dispersed metal sites and special electronic structures achieve improved reactivity.

Benefits of technology

It realizes fast, high sensitivity and wide detection range SCN-detection and dye degradation, simplifies the operation process, overcomes the shortcomings of the prior art, and provides a visual, colorimetric detection system that is not required by the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114129A_ABST
    Figure CN119114129A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a bimetallic MnFe-N-C monatomic nano-enzyme and application of the bimetallic MnFe-N-C monatomic nano-enzyme in SCN <-> detection and dye degradation, and belongs to the technical field of SCN <-> detection and dye degradation. The preparation method specifically comprises the following steps: step (1), preparing a MnFe-N-C monatomic nano-enzyme material; (2) preparing a MnFe-N-C monatomic nano-enzyme material for colorimetric detection of SCN <->; step (3), preparing a MnFe-N-C monatomic nano-enzyme material degradation dye; and (4) preparing a colorimetric sensing working curve of the MnFe-N-C monatomic nano enzyme for detecting the thiocyanate. The bimetallic MnFe-N-C monatomic nano-enzyme is prepared by adopting a green and simple synthesis process, the cost is greatly reduced, the bimetallic MnFe-N-C monatomic nano-enzyme has the characteristics of high stability and high catalytic activity, SCN-is detected by a colorimetric method, and dye rhodamine B is rapidly degraded by activating peroxymonosulfate. The method has the advantages of higher sensitivity, wider detection range, higher detection speed, simplicity in operation and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to SCN - The invention relates to the technical field of detection and dye degradation, and specifically relates to a preparation method of a bimetallic MnFe-NC single-atom nanozyme and its application in SCN - Detection and application of dye degradation. Background Art

[0002] Thiocyanate (SCN - ) is a pseudohalogen, mainly found in textile dyeing, hydrometallurgy, electroplating and photoprocessing in industrial processes, as well as cigarette smoke and automobile exhaust in daily life. It is an anionic pollutant widely present in water. Due to the accumulation of environmental effects, it has a serious impact on aquatic plants and animals. In addition, due to SCN - It is a component of the lactoperoxidase system and is often used as an antioxidant additive as an antibacterial and preservative, which leads to its presence in foods such as milk and cheese. - It can adversely affect host cells by blocking the thyroid gland's absorption of iodine, leading to reduced thyroid hormone concentrations and iodine deficiency, ultimately inducing goiter. It is also associated with Alzheimer's disease, Parkinson's disease, cardiovascular disease, cirrhosis, cancer, and Down syndrome. In addition, SCN in water and food - It can be converted into highly toxic cyanide through radiation and chlorination, causing serious environmental problems and human health hazards. - The detection of is crucial in environmental, medical and life science research.

[0003] Nanozyme is a kind of mimetic enzyme. Due to its unique structure, large contact area, excellent catalytic function, high catalytic efficiency and stability, it is widely used in pharmaceutical production, chemical manufacturing, food processing, environment, etc. In order to make full use of the efficient catalytic activity of nanozymes, it is expected to be used not only for sensing and detecting environmental pollutants, but also for the degradation of organic pollutants such as dyes. It is well known that the hydroxyl radicals produced in the Fenton-like reaction can easily degrade dyes, but there are still some limitations in the degradation of dyes in the Fenton-like system, such as the extremely limited pH range of the reaction (pH range is about 2-4), and the difficulty of catalyst recovery, which greatly limits the practical application of the Fenton-like system in dye degradation. Therefore, if the highly dispersed metal sites, special electronic structure, good pH stability and excellent catalytic performance of nanozymes are used in the dye degradation process, it is expected to overcome the above shortcomings in the dye degradation process. Compared with single metal nanozymes, bimetallic nanozymes achieve improved reactivity through metal-metal complementarity and multi-point activation.

[0004] So far, SCN -There are many methods for the determination of SCN, such as electrospray ion mobility spectrometry, gas chromatography, capillary electrophoresis, electrochemistry, inductively coupled plasma atomic emission spectrometry, fluorescence spectroscopy, etc. However, these methods have some disadvantages, including time-consuming, complex and cumbersome operations, requiring expensive instruments and skilled technical operators. Compared with the above methods, colorimetry has become one of the research hotspots for detection due to its simplicity, visualization, no equipment required, and fast detection speed. Therefore, constructing SCN - Colorimetric detection and degradation systems of organic dyes are of great significance. Summary of the invention

[0005] The technical problem to be solved by the present invention is to propose a preparation method of a bimetallic MnFe-NC single-atom nanozyme and its application in SCN - Detection and application of dye degradation.

[0006] To achieve its purpose, the present invention adopts the following technical solutions:

[0007] A method for preparing a bimetallic MnFe-NC single-atom nanozyme comprises the following steps:

[0008] ① Preparation of bimetallic metal framework material ZIF-MnFe: Aniline and 2-methylimidazole were dispersed in deionized water according to the prescribed ratio, and ultrasonically dissolved at room temperature to obtain a uniform solution, which was marked as solution A;

[0009] According to the specified proportion, Zn(NO3)2, MnCl2 4H2O and FeCl2 4H2O were mixed with deionized water and added to solution A;

[0010] After the obtained mixture was stirred at room temperature for 4 h, the ZIF-MnFe powder was collected by centrifugation washing with water, and then dried at 60° C. to obtain the bimetallic metal framework material ZIF-MnFe;

[0011] ② Preparation of MnFe-NC:

[0012] The dried bimetallic metal framework material ZIF-MnFe was heated from room temperature to 900°C under an argon atmosphere at a heating rate of 5°C / mmin and maintained at this temperature for 2h to obtain the bimetallic single-atom nanozyme MnFe-NC.

[0013] Preferably, in step ①, the ratio of aniline to deionized water is 0.03-0.04 mL:1 mL, and the solid-liquid ratio of 2-methylimidazole to deionized water is 0.03-0.04 g:1 mL.

[0014] Preferably, in step ①, the ratio of Zn(NO3)2 to deionized water is 0.02-0.035 g:1 mL, the ratio of MnCl2 4H2O to deionized water is 0.001-0.002 g:1 mL; the ratio of FeCl24H2O to deionized water is 0.0009-0.001 g:1 mL.

[0015] Another technical solution of the present invention is a bimetallic MnFe-NC single-atom nanozyme in SCN - The application of detection and dye degradation includes the following steps:

[0016] Step (1): preparing MnFe-NC single-atom nanozyme material;

[0017] Step (2): Preparation of MnFe-NC single-atom nanozyme material for colorimetric detection of SCN - ;

[0018] Step (3): preparing MnFe--NC single-atom nanozyme material to degrade dye;

[0019] Step (4): Preparation of MnFe-NC single-atom nanozyme for SCN detection - Colorimetric sensing working curve.

[0020] Preferably, the step (2) prepares MnFe-NC single-atom nanozyme material for colorimetric detection of SCN - include;

[0021] ① Different concentrations of SCN - The aqueous solution was added into 3 mL of buffer solution system;

[0022] ② In step ①, MnFe-NC, TMB and H2O2 are added in a prescribed proportion;

[0023] ③After incubation at room temperature for 10 min, the absorption spectrum of the reaction solution was recorded at 652 nm.

[0024] Preferably, the step (3) of preparing the MnFe-NC single-atom nanozyme material for degrading dyes comprises:

[0025] ① Add MnFe-NC to Rhodamine B in the prescribed ratio to allow it to diffuse completely;

[0026] ② Add PMS to initiate degradation reaction;

[0027] ③ Extract a certain amount of suspension at a preset time and filter it with a 0.22 μm mixed fiber membrane using a syringe;

[0028] ④ Use an ultraviolet spectrophotometer to measure the absorbance of the filtrate at 554nm.

[0029] Further preferably, the step (4) prepares MnFe-NC single-atom nanozyme to detect SCN - The colorimetric sensing working curve includes:

[0030] ① Aqueous solutions of SCN with different concentrations were added into 3 mL of buffer solution system;

[0031] ② Add MnFe-NC, TMB and H2O2 in step ①;

[0032] ③ After incubation at room temperature for 10 min, the absorbance of the reaction solution at 652 nm was recorded using a UV spectrophotometer;

[0033] ④Use the working curve method to obtain the SCN in the sample to be tested - concentration.

[0034] Preferably, in the step (2), the amount of MnFe-NC added in step ② is 10 μL, the amount of TMB added is 70 μL, and the amount of H2O2 added is 15 μL.

[0035] Preferably, in step (3) in step ①, the amount of MnFe-NC added is 500 μL 3 mgmI -1 , the amount of rhodamine B added was 0.02mgmI -1 30mL, the PMS added in step ② is 180μL 30mg mL -1 .

[0036] Further preferably, in step (4), the amount of MnFe-NC added in step ② is 10 μL 2 mg mL -1 , 70 μL 7.5 mmol L 3,3′,5,5′-tetramethylbenzidine (TMB) was added -1 , the amount of H2O2 added was 15 μL 250 mmol L -1 .

[0037] Beneficial effects of the present invention:

[0038] 1. The present invention constructs a colorimetric sensing platform based on bimetallic MnFe-NC single-atom nanozymes to achieve accurate quantitative detection of SCN - purpose;

[0039] 2. The present invention uses bimetallic MnFe-NC single-atom nanozymes to activate PMS to achieve rapid degradation of the dye Rhodamine B. This method has the advantages of high sensitivity, wide detection range, fast detection speed and simple operation, and can be used for rapid detection and degradation of actual pollutants;

[0040] 3. Build SCN - The colorimetric detection and degradation system of organic dyes are of great significance, and provide further reference for subsequent research and exploration in related fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] For ease of explanation, the present invention is described in detail with reference to the following specific embodiments and the accompanying drawings.

[0042] Figure 1 TEM images of NC (A), Mn-NC (B), Fe-NC (C) and MnFe-NC (D);

[0043] Figure 2 XPS graphs of NC (A), Mn-NC (B), Fe-NC (C) and MnFe-NC (D);

[0044] Figure 3 For the study of the peroxidase-like activity of the catalyst;

[0045] Figure 4 is the degradation of Rhodamine B in different reaction systems (A), the reaction rate constants of NC, Mn-NC, Fe-NC and MnFe-NC. DETAILED DESCRIPTION

[0046] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments; in the following description, specific details such as specific configurations are provided only to help fully understand the embodiments of the present invention. Therefore, it should be clear to those skilled in the art that various changes and modifications can be made to the embodiments described herein without departing from the scope and spirit of the present invention.

[0047] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features of the embodiments may be combined with each other.

[0048] Unless otherwise specified, the materials, practices and experimental equipment involved in the implementation cases of the present invention are all in line with commercially available products in the relevant chemical and biotechnology fields.

[0049] This embodiment provides a bimetallic MnFe-NC single-atom nanozyme in SCN - The application of detection and dye degradation includes the following steps:

[0050] Step (1): preparing MnFe-NC single-atom nanozyme material;

[0051] Step (2): Preparation of MnFe-NC single-atom nanozyme material for colorimetric detection of SCN - ;

[0052] Step (3): preparing MnFe--NC single-atom nanozyme material to degrade the dye Rhodamine B;

[0053] Step (4): Preparation of MnFe-NC single-atom nanozyme for SCN detection - Colorimetric sensor working curve;

[0054] The step (1) of preparing the MnFe-NC single-atom nanozyme material comprises:

[0055] ① Preparation of bimetallic metal framework material ZIF-MnFe

[0056] First, 2.92 mL of aniline and 2.62 g of 2-methylimidazole were dispersed in 80 mL of deionized water and ultrasonically dissolved at room temperature to obtain a uniform solution, which was marked as solution A. Secondly, 2.38 g of Zn(NO3)2, 0.095 g of MnCl2 4H2O and 0.0795 g of FeCl2 4H2O were mixed with 80 mL of deionized water and added to solution A. After the resulting mixture was stirred at room temperature for 4 h, the bimetallic metal framework material ZIF-MnFe powder was collected by centrifugal washing with water, and then dried at 60 ° C to obtain the bimetallic metal framework material ZIF-MnFe. The method for synthesizing ZIF-Mn and ZIF-Fe is the same, except that FeCl2 4H2O or MnCl2 4H2O is not added.

[0057] ② Preparation of bimetallic single-atom nanozymes MnFe-NC

[0058] The dried bimetallic metal framework material ZIF-MnFe was heated from room temperature to 900°C in an argon atmosphere at a heating rate of 5°C / min and maintained at this temperature for 2 hours to obtain the bimetallic single-atom nanozyme MnFe-NC. The method for synthesizing Mn-NC and Fe-NC is the same.

[0059] Preferably, the step (2) prepares MnFe--NC bimetallic single-atom nanozyme material for colorimetric detection of SCN - include:

[0060] ① Different concentrations of SCN - The aqueous solution was added into 3 mL of buffer solution system;

[0061] ②Add 10 μL of 2 mg mL -1 MnFe-NC, 70 μL 7.5 mmol L -1 TMB and 15 μL 250 mmol L -1 H2O2;

[0062] ③After incubation at room temperature for 10 min, the absorption spectrum of the reaction solution was recorded at 652 nm.

[0063] Preferably, the step (3) of preparing the MnFe-NC single-atom nanozyme material for degrading dyes comprises:

[0064] ① Add 500 μL of 3 mg mL -1 MnFe-NC was added to 0.02 mg mL -1 30mL of Rhodamine B, allowing it to diffuse completely;

[0065] ②Add 180 μL 30 mg mL -1 PMS triggers degradation reactions;

[0066] ③ Extract a certain amount of suspension at a preset time and filter it with a 0.22 μm mixed fiber membrane using a syringe;

[0067] ④ Use an ultraviolet spectrophotometer to measure the absorbance of the filtrate at 554nm.

[0068] Further preferably, the step (4) prepares MnFe-NC single-atom nanozyme to detect SCN - The colorimetric sensing working curve includes:

[0069] ① Different concentrations of SCN - The aqueous solution was added into 3 mL of buffer solution system;

[0070] ②Add 10 μL of 2 mg mL -1 MnFe-NC, 70 μL 7.5 mmol L -1 TMB and 15 μL 250 mmol L -1 H2O2;

[0071] ③ After incubation at room temperature for 10 min, the absorbance of the reaction solution at 652 nm was recorded using a UV spectrophotometer;

[0072] ④Use the working curve method to obtain the SCN in the sample to be tested - concentration.

[0073] Figure 1 The transmission electron microscopy (TEM) of NC (A), Mn-NC (B), Fe-NC (C) and MnFe-NC (D) in step (1); NC presents an irregular morphology; Mn-NC presents a regular tetrahedral structure ( Figure 1 B); Figure 1 As shown in Figure C, after pyrolysis, Fe-NC does not have highly crystalline iron, indicating the presence of single-atom iron ( Figure 1 C); Figure 1As shown in D, no manganese iron particles were observed, indicating that manganese iron in MnFe-NC may exist in the form of single atoms; these results also illustrate the successful preparation of NC, Mn-NC, Fe-NC and MnFe-NC materials.

[0074] Figure 2 The X-ray photoelectron spectra (XPS) of NC (A), Mn-NC (B), Fe-NC (C) and MnFe-NC (D) in step (1) show that for NC, only N and C exist. After high-temperature calcination, the elements of Mn-NC increase to Mn, N, and C, and the elements of Fe-NC increase to Fe, N, and C, indicating that Mn-NC and Fe-NC are calcined successfully. After calcination of MnFe-ZIF, it can be clearly observed that Mn, Fe, N, and C coexist in MnFe-NC, indicating that MnFe-NC is successfully synthesized.

[0075] Figure 3 For step (2) NC, Mn-NC, Fe-NC) and MnFe-NC, the peroxidase-like activity is catalyzed by TMB as the substrate for the oxidation reaction, such as Figure 3 As shown in the figure, when only TMB, H2O2 and TMB+H2O2 are present in the reaction system, the change in absorbance can be basically ignored; after adding NC to the system with TMB+H2O2, the absorbance does not change significantly, indicating that NC has no peroxidase activity. However, in the presence of Fe-NC and Mn-NC, the absorbance value increases due to the catalyst catalyzing TMB to form oxidized TMB, proving that metal doping can improve catalytic activity. Compared with single-atom catalysts, the peroxidase activity of the bimetallic single-atom catalyst MnFe-NC is improved, which may be due to the synergistic effect of manganese and iron single atoms.

[0076] Figure 4 is the degradation and reaction rate constant of Rhodamine B in different reaction systems in step (3). In the presence of only PMS or NC, the degradation of Rhodamine B is negligible; only about 30% of Rhodamine B is removed by Mn-NC; in the Fe-NC / PMS system, about 70% of Rhodamine B is removed within 10 min. However, in the MnFe-NC / PMS system, PMS activated by MnFe-NC achieves about 100% removal of Rhodamine B within 10 min. The results show that MnFe-NC is more effective in activating PMS to degrade Rhodamine B than Mn-NC and Fe-NC. In order to evaluate the catalytic performance, the reaction rate constant (k) ( Figure 4 B), the k value follows that of MnFe-NC (0.254min -1 )>Fe-NC(0.110min-1 )>Mn-NC(0.0345min -1 )NC(0.0064min -1 ), which is consistent with the order of oxidase-like activity.

[0077] Those skilled in the art to which the present application belongs may make various modifications or additions to the specific embodiments described or replace them in a similar manner, but they will not deviate from the inventive concept of the present application or exceed the scope defined by the attached claims.

Claims

1. A method for preparing bimetallic MnFe-NC single-atom nanozyme, It is characterized in that The steps include: ① Preparation of bimetallic metal framework nanomaterial ZIF-MnFe: Aniline and 2-methylimidazole were dispersed in deionized water according to the prescribed ratio, and ultrasonically dissolved at room temperature to obtain a uniform solution, which was marked as solution A; According to the prescribed ratio, Zn(NO 3 ) 2 、MnCl 2 4H 2 O and FeCl 2 4H 2 O was mixed with deionized water and added to solution A; The resulting mixture was stirred at room temperature for 4 h, and the ZIF-MnFe powder was collected by centrifugation and then heated at 60 o C drying to obtain the bimetallic metal framework nanomaterial ZIF-MnFe; ② Preparation of MnFe-NC: The dried bimetallic metal framework nanomaterial ZIF-MnFe was heated from room temperature to 900 °C in an argon atmosphere at a rate of 5 o C / min and kept at this temperature for 2 h to obtain the bimetallic single-atom nanozyme MnFe-NC.

2. The method for preparing the bimetallic MnFe-NC single-atom nanozyme according to claim 1, It is characterized in that In step ①, the ratio of aniline to deionized water is 0.03-0.04 mL:1 mL, and the solid-liquid ratio of 2-methylimidazole to deionized water is 0.03-0.04 g:1 mL.

3. The method for preparing the bimetallic MnFe-NC single-atom nanozyme according to claim 1, It is characterized in that In step ①, the Zn(NO 3 ) 2 The ratio of MnCl to deionized water is 0.02-0.035 g:1 mL. 2 4H 2 O and deionized water ratio is 0.001-0.002 g: 1 mL; the FeCl 2 4H 2 The ratio of O to deionized water is 0.0009-0.001 g:1 mL.

4. A bimetallic MnFe-NC single-atom nanozyme prepared by any one of the preparation methods of claims 1 to 3 in SCN - Detection and application of dye degradation, It is characterized in that The steps include: Step (1): preparing MnFe-NC single-atom nanozyme material; Step (2): Preparation of MnFe-NC single-atom nanozyme material for colorimetric detection of SCN - ; Step (3): preparing MnFe-NC single-atom nanozyme material to degrade the dye Rhodamine B; Step (4): Preparation of MnFe-NC single-atom nanozyme for SCN detection - Colorimetric sensing working curve.

5. The use according to claim 4, It is characterized in that The step (2) is to prepare the MnFe-NC single-atom nanozyme material for colorimetric detection of SCN - include: ① Different concentrations of SCN - The aqueous solution was added into 3 mL of buffer solution system; ②In step ①, add 2 mg mL -1 MnFe-NC, 7.5 mmol L -1 3,3',5,5'-Tetramethylbenzidine (TMB) and 250 mmol L -1 H 2 O 2 ; ③After incubation at room temperature for 10 min, the absorption spectrum of the reaction solution was recorded at 652 nm.

6. The use according to claim 4, It is characterized in that The step (3) of preparing the MnFe-NC single-atom nanozyme material for dye degradation comprises: ① Add MnFe-NC to Rhodamine B in the prescribed ratio to allow it to diffuse completely; ② Add peroxymonosulfate (PMS) to initiate the degradation reaction; ③ Extract a certain amount of suspension at a preset time and filter it with a 0.22 μm mixed fiber membrane using a syringe; ④Use UV spectrophotometer to measure the absorbance of the filtrate at 554 nm.

7. The use according to claim 4, It is characterized in that The step (4) is to prepare MnFe-NC single-atom nanozyme to detect SCN - The colorimetric sensing working curve includes: ① Different concentrations of SCN - The aqueous solution was added into 3 mL of buffer solution system; ②In step ①, add MnFe-NC, TMB and H 2 O 2 ; ③ After incubation at room temperature for 10 min, the absorbance of the reaction solution at 652 nm was recorded using a UV spectrophotometer; ④Use the working curve method to obtain the SCN in the sample to be tested - concentration.

8. The use according to claim 5, It is characterized in that In step ②, 10 μL of MnFe-NC, 70 μL of TMB, and 10 μL of H 2 O 2 is 15 μL.

9. The use according to claim 6, It is characterized in that In step ①, 500 μL 3 mg / mL MnFe-NC was added. -1 , the amount of rhodamine B added was 0.02 mg mL -1 30 mL, the PMS added in step ② is 180 μL 30 mg mL -1 .

10. The use according to claim 7, It is characterized in that The MnFe-NC added in step ② was 10 μL 2 mg mL -1 , 70 μL 7.5mmol L TMB was added -1 , added H 2 O 2 15 μL 250 mmol L -1 .

Citation Information

Cited By

  • Novel Fe-C-N-coated Au material and preparation method and application thereof

    CN121315249A

  • Method for colorimetric detection of KSCN by graphite-phase carbon nitride nano-enzyme

    CN121783959A